2015
DOI: 10.1111/aji.12356
|View full text |Cite
|
Sign up to set email alerts
|

NK22 Cells in the Uterine Mid-Secretory Endometrium and Peripheral Blood of Women with Recurrent Pregnancy Loss and Unexplained Infertility

Abstract: Endometrial NK22 cells are differently regulated in women with URPL and UI. Women with URPL have higher level of NK22 cells with a potential to induce NK2 shift than women with UI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…In conclusion, we have demonstrated the importance of NKp46 in reproduction. We have reported decreased expression of NKp46 in peripheral blood in women with previous reproductive failures, such as RPL and implantation failure, 16,26,27,34,35 in peritoneal fluid in women with pelvic endometriosis, 36 and in peripheral blood in pregnant women with gestational diabetes mellitus. 37 These studies suggest that regulation of NKp46 expression in various types of NK cells may be one of the key factors in reproductive failure.…”
Section: Discussionmentioning
confidence: 91%
“…In conclusion, we have demonstrated the importance of NKp46 in reproduction. We have reported decreased expression of NKp46 in peripheral blood in women with previous reproductive failures, such as RPL and implantation failure, 16,26,27,34,35 in peritoneal fluid in women with pelvic endometriosis, 36 and in peripheral blood in pregnant women with gestational diabetes mellitus. 37 These studies suggest that regulation of NKp46 expression in various types of NK cells may be one of the key factors in reproductive failure.…”
Section: Discussionmentioning
confidence: 91%
“…suggested that NK22 cells produce IL‐22 and other cytokines that prevent inflammation and protect mucosal sites in tonsils or Peyer's patches . We previously reported the higher production of UE NK22 cells in women with RPL . NK22 cells are presumed to increase to normalize or regulate cytokine production in women with RPL.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that NK22 cells in the human UE express NKp46 . Previously, we reported that NK22 cells express NKp46 …”
Section: Introductionmentioning
confidence: 99%
“…These findings shed some light on the relationships existing between NKp46 ? NK cells, production of cytokines (IFNc and TNFa) by NK cells, and NK22 cells [41]. We speculated that in normal pregnancy, NK22 cells could produce IL-22 whereas conventional NK cells produce IFNc and TNFa.…”
Section: Nk22 Cells and Reproductionmentioning
confidence: 99%
“…We have evaluated the physiological role of NK22 cells in women with and without unexplained RPL using samples of pre-pregnancy peripheral blood and midsecretory uterine endometrium [41]. The relative proportions of NK22 cells in both peripheral blood and uterine endometrium were significantly higher in women with RPL than in women without RPL.…”
Section: Nk22 Cells and Reproductionmentioning
confidence: 99%